The Effect of Combination of Organic Fertilizer and Rice Husk Biochar on Growth, Production, Available N and N Absorption of Soybean (Glycine Max L) in Ultisol Soil - Panjaitan, Ernitha (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This research was conducted on Jl. Bunga Sedap malam XVIII Medan North Sumatra with an altitude of ± 30 meters above sea level (masl), this research took place from February to April 2022. This study used the Non Factorial Randomized Group Design method. Factor B1 = Control, B2 = Organic fertilizer 15 tons/ha, B3 = Rice husk biochar 15 tons/ha, B4 = Organic fertilizer 12.5 tons/ha + Rice husk biochar 2.5 tons/ha, B5 = Organic fertilizer 10 tons/ha + Rice husk biochar 5 tons/ha, B6 = Organic fertilizer 7.5 tons/ha + Biochar rice husk 7.5 tons/ha, B7 = Organic fertilizer 5 tons/ha + Biochar rice husk 10 tons/ha, B8 = Organic fertilizer 2.5 tons/ha + Biochar rice husk 12.5 tons/ha. From the results of the study it can be concluded that the treatment of cow organic fertilizer and rice husk biochar had a significant effect on plant height, number of branches, root nodules, wet weight of pods/plot, dry weight of pods/plot, soil pH, base saturation (KB), and N absorbed, but had no significant effect on the number of filled pods, number of empty pods, cation exchange capacity (CEC), and N available. The average number of filled pods was highest in treatment B4 (36.67%) and lowest in treatment B1 (1.33%). The highest average cation exchange capacity (CEC) was found in treatment B2 (18.76m3/100g) and the lowest average was found in treatment B6 (10.79me/100g). The highest average available N was found in treatment B2 (4.13%) and the lowest was found in treatment B8 (3.15%).